A novel rabbit model of Duchenne muscular dystrophy generated by CRISPR/Cas9 - Tingting Sui; Yeh Siang Lau; Di Liu; Tingjun Liu; Li Xu; Yandi Gao; Liangxue Lai; Zhanjun Li; Renzhi Han (The Company of Biologists, 2018)
Duchenne muscular dystrophy (DMD) is an X-linked muscle-wasting disorder caused by mutations in the dystrophin gene, with an incidence of 1 in 3500 in new male births. Mdx mice are widely used as an animal model for DMD. However, these mice do not faithfully recapitulate DMD patients in many aspects, rendering the preclinical findings in this model questionable. Although larger animal models of DMD, such as dogs and pigs, have been generated, usage of these animals is expensive and only limited to several facilities in the world. Here, we report the generation of a rabbit model of DMD by co-injection of Cas9 mRNA and sgRNA targeting exon 51 into rabbit zygotes. The DMD knockout (KO) rabbits exhibit the typical phenotypes of DMD, including severely impaired physical activity, elevated serum creatine kinase levels, and progressive muscle necrosis and fibrosis. Moreover, clear pathology was also observed in the diaphragm and heart at 5 months of age, similar to DMD patients. Echocardiography recording showed that the DMD KO rabbits had chamber dilation with decreased ejection fraction and fraction shortening. In conclusion, this novel rabbit DMD model generated with the CRISPR/Cas9 system mimics the histopathological and functional defects in DMD patients, and could be valuable for preclinical studies. This article has an associated First Person interview with the first author of the paper.